Kebijakan Pemerintah Daerah dalam Pelestarian Kesenian Tradisional di Kabupaten Jember - Widiyanto, Dayfrikoe (Pusat Pengkajian Pancasila dan Konstitusi (PUSKAPSI) FH UNEJ, 2021)
There are government policies to ensure the successful implementation of the concept of regional autonomy, once again a strong commitment and consistent leadership from the central government are needed. Law Number 23 of 2014 concerning Regional Government as amended several times, most recently by Law Number 9 of 2015 concerning the Second Amendment to Law Number 23 of 2014 concerning Regional Government (